Enantioresolution of (RS)‐baclofen by liquid chromatography: A review. (13th October 2016) - Batra, Sonika; Bhushan, Ravi
Abstract: Baclofen is a commonly used racemic drug and has a simple chemical structure in terms of the presence of only one stereogenic center. Since the desirable pharmacological effect is in only one enantiomer, several possibilities exist for the other enantiomer for evaluation of the disposition of the racemic mixture of the drug. This calls for the development of enantioselective analytical methodology. This review summarizes and evaluates different methods of enantioseparation of ( RS )‐baclofen using both direct and indirect approaches, application of certain chiral reagents and chiral stationary phases (though very expensive). Methods of separation of diastereomers of ( RS )‐baclofen prepared with different chiral derivatizing reagents (under microwave irradiation at ease and in less time) on reversed‐phase achiral columns or via a ligand exchange approach providing high‐sensitivity detection by the relatively less expensive methods of TLC and HPLC are discussed. The methods may be helpful for determination of enantiomers in biological samples and in pharmaceutical formulations for control of enantiomeric purity and can be practiced both in analytical laboratories and industry for routine analysis and R&D activities.